Imagery in Dover Beach Poem: Psychoanalytic Perspective - Euis - Meinawati; Lisnawati - Lisnawati (Wanastra: Jurnal Bahasa dan Sastra, 2020)
Poetry/poem as one of a literary works is definitely an interesting subject to be analyzed. In a poem there are some elements that are valuable as an analysis source. One of them is Imagery. Imagery is used in a poem to help the readers in understanding and comprehending the whole poem because through imagery the readers can imagine every word, they are reading in the poem so they can see, feel, touch, hear, taste and smell the thing that is described by the speaker/poet. Literary work also can be analyzed by its extrinsic elements which is literary criticism or multi disciplines. One of phenomenal literary criticism is psychoanalytic perspective. Through psychoanalytic perspective the work of literature reveals the psychoanalytic aspect of the depth true feeling of the author. The purpose of this analysis is to know what kinds of imagery contained in Dover Beach poem written by Matthew Arnold. The method of this analysis is using descriptive and qualitative methods by reading and underlining the line and stanza contains imagery and every line and stanza reveals the psychoanalytic aspect. The result of this analysis is the writer finds out there are some imagery contained in Dover Beach poem. Dover Beach poem contains Visual Imagery, Olfactory Imagery, Auditory Imagery, Kinesthetic Imagery, and Organic Imagery. In Dover Beach poem are found some of psychoanalytic aspects such as unconscious and the id, ego, and superego in Dover Beach poem